FORENSIC MEDICAL ASSESSMENT CLINIC OF MORPHOLOGICAL CHANGES IN CASE OF CARBON MONOXIDE POISONING DUE TO ALCOHOL INTOXICATION - Yakubov, K.H; Nasirov; Nasirov, T.K (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: Forensic clinical morphological changes in acute poisoning of carbon dioxide on the background of alcohol intoxication and timing of poisoning. Material and methods: The results of the forensic medical examination of corpses and the history of the victims of acute carbon monoxide poisoning were analyzed in 135. Quontitotive indications of carboxyhemoglobin in the blood Fretvurst, and Minex were detected using spectrophotometrichmethods.Results: Clinical and morphological effects on acute poisoning of carbon oxidized against the background of alcohol intoxication were systematized and the main stages of tanatogenesis were identified. Conclusions: Ethyl alcohol weakness carboxyhemoglobin’s toxic effect in small amounts, in large quantities, it has been discovered that carboxyhemoglobin can exacerbate the toxic effects and increase the risk of death